Similarities and Differences Between Phonological Phenomena in Arabic and Tamil Languages: Syllable-Focused Study - MCS. Shathifa; Asem Shehadeh Ali (Diwan Media Pustaka, 2024)
Phonological phenomena mean the rules and phonetic characteristics that help to build words and vocabulary, create and use speech, and differentiate between them according to context. Accordingly, in a language there are phonetic units that are studied at non-structual level and structual level. They have an impact on teaching the Arabic language to native speakers in general and to non-native speakers in particular. Errors in phonetic phenomena lead to linguistic errors. The research problem is defined by the question: “Is there a similarity in the syllable system of phonological phenomena between the Arabic and Tamil languages, which are from two different language families? This research aims to clarify the syllabic system of phonological phenomena between Arabic and Tamil languages, and to identify the similarities and differences in syllabic system of phonological phenomena between them. This research relies on qualitative methodology under contrastive descriptive analysis to identify similarities and differences in phonological phenomena between the languages. Secondary data were gathered from books, researches and literary studies. This research titled “Similarities and differences between phonological phenomena in Arabic and Tamil languages: syllable-focused study” finds that the syllables are divided based on length and the closing and opening in the two languages are in the same form. There are no two consecutive consonants at the beginning of the word in them. In terms of differences, the Arabic syllable begins with a consonant only, and there is no Arabic syllable that begins with a vowel, while the Tamil syllable begins with a consonant and a vowel. More than two consonants can not exceed in the middle of the Arabic word, meanwhile can exceed in Tamil. The places where the syllables occur in the two languages are differed according to characteristics of both languages. The Arabic syllable system is very similar to Tamil language.